Relacyjne podejście do zarządzania łańcuchem dostaw z perspektywy związku kapitału relacyjnego ze współpracą = A relational approach to supply chain management from the perspective of the relationship between relational capital and cooperation - Danielak, Wiesław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the factors influencing the relational approach to business-to-business (B2B) supply chain management, showing the relationship between relational capital and cooperation. The theoretical part presents factors influencing the relational management of the business to business (B2B) supply chain based on literature studies. Using the literature study method, the factors influencing the logistic management of the B2B supply chain were shown.
Keywords: relacje z dostawcami; zarządzanie relacjami; łańcuch dostaw; kapitał relacyjny; współpraca; relationships with suppliers; relationship management; supply chain; relationship capital; cooperation